The influence of environmental variables in the reproductive performance of Macrobrachium amazonicum (Heller, 1862) (Caridea: Palaemonidae) females in a continental population - Pantaleão, João Alberto Farinelli [UNESP]; Carvalho-Batista, Abner [UNESP]; Teodoro, Sarah S. A. [UNESP]; Costa, RogéRio C. [UNESP] (FapUNIFESP (SciELO), 2018)
Macrobrachium amazonicum is a commercially important freshwater prawn with a high degree of reproductive plasticity. The species is classified into two groups: coastal populations, with larger individuals exhibiting high fecundity and needing brackish water for larval development; and continental populations, with smaller specimens exhibiting low fecundities and completing metamorphosis in freshwater. The objective of this study was to investigate the influence of environmental factors in the fecundity, egg size and volume, and reproductive output in females of M. amazonicum from a continental population during a two-year period. We also compared our results with those obtained for other continental and coastal populations. Reproductive parameters differed markedly between continental and coastal populations in most cases. The continental population studied here, however, exhibited reproductive characteristics similar to those of coastal populations. The present study found a correlation between the reproductive parameters and the environmental variables analyzed. This result corroborates the hypothesis that wide variation in reproductive parameters in the geographical distribution of M. amazonicum is related to the environmental characteristics in which populations are inserted. We suggest that further studies could investigate the potential of continental populations for aquaculture, which could significantly reduce production costs.
Keywords: Abiotic factors; Amazon river prawn; Reproductive output; Shrimp; Tietê